Breadth And Depth Of Academic Vocabulary Knowledge : Assessing Their Roles In Academic Reading And Writing Of English Language Learners - Lee, Chew Wei (Universiti Malaysia Sarawak, (UNIMAS), 2017)
The study investigated the relationship between English language learner's (ELL) academic vocabulary and their performance in academic reading and writing. The objectives were to determine the correlation between academic vocabulary knowledge and the academic reading comprehension and writing and the extent to which academic vocabulary knowledge contribute to academic reading and writing performance. Quantitative research design was employed in the study. Vocabulary Levels Test (VLT), Productive Vocabulary Levels Test (PVLT), Depth of Vocabulary Knowledge Test (DVK), Reading Comprehension (RC) test and Writing test were administered to 90 UNIMAS undergraduates. Pearson correlation analysis showed that there was a significant correlation between breadth and depth of academic vocabulary with academic reading and writing performance of ELL. Vocabulary depth had a stronger correlation with academic reading comprehension while vocabulary breadth had a stronger correlation with academic writing. The multiple linear regression results revealed that both dimensions of academic vocabulary knowledge contributed moderately to academic reading comprehension and writing performance although vocabulary depth contributed more to academic reading comprehension while vocabulary breadth contributed more to academic writing performance. Both breadth and depth of academic vocabulary knowledge were rather significant predictors of academic reading and writing performance of learners and therefore a combination of these two dimensions will aid in better performance. Thus, the teaching and learning of the English language should emphasize in vocabulary building in terms of enriching learners' vocabulary storage as well as improving the usage of vocabulary in context by understanding the meaning